Near-infrared triggered strand displacement amplification for MicroRNA quantitative detection in single living cells. Issue 7 (13th December 2017) - Dai, Wenhao; Dong, Haifeng; Guo, Keke; Zhang, Xueji
Abstract : Two hairpin functionalized AuNRs were designed for NIR-laser triggered strand displacement amplification for microRNA quantitative analysis in single living cells. Abstract : As an important modulator of gene expression, microRNA (miRNA) has been described as a promising biomarker for the early diagnosis of cancers. A non-invasive method for real-time sensitive imaging and monitoring of miRNA in living cells is in urgent demand. Although some amplified methods have been developed, few can be programmed to assemble single intelligent nanostructures to realize sensitive intracellular miRNA detection without extra addition of an enzyme or catalytic fuel. Herein, two programmable oligonucleotide hairpin probe functionalized gold nanorods (THP-AuNRs) were designed to develop a near-infrared (NIR) laser triggered target strand displacement amplification (SDA) approach for sensitive miRNA imaging quantitative analysis in single living cells and multicellular tumor spheroids (MCTSs). Such a NIR-triggered SDA strategy achieves facile and sensitive monitoring of a model oncogenic miRNA-373 in various cancer lines and MCTS simulated tumor tissue. Notably, using a linear regression equation derived from miRNA mimics, a quantitative method of miRNA in single living cells was realized due to the high sensitivity. This provides a new way for sensitive real-time monitoring of intracellular miRNA, and may be promising for miRNA-based biomedical applications.